TEKNOLOGI PENGOLAHAN PUPUK ORGANIK PADA KELOMPOK TANI SUNGKAI PERMAI DI KELURAHAN LAMBUNG BUKIK KOTA PADANG - Benni Satria; Syahyan Raesi; Afrima Sari; Armansyah Armansyah; Indra Dwipa; Aprisal Aprisal; Ferry Lismanto Syaiful; Ardi Ardi (LPPM Universitas Andalas, 2020)
The people of Lambung Bukik Village, Pauh Subdistrict, Padang City, mostly work on horticultural crops, secondary crops, raising cattle, and chickens. Agriculture in this area uses mostly inorganic fertilizers and organic fertilizers. This results in the high need for farmers for inorganic fertilizers. The activity's objectives are 1. to obtain an organic production module by utilizing horticultural agricultural waste, secondary crops, and cow dung, 2. analyzing the organic fertilizer content, 3). obtain organic fertilizer containing high nutrient elements and 4. obtain organic fertilizer derived from organic fertilized waste material with EM4, MOL, and Trichoderma sp. Activities were carried out in the UPPO Sungkai Permai farming community through organic fertilizer processing technology. Participants in this activity are members of farmer groups, community leaders, and accompanied by Andalas University students. The activity methods applied are 1. training and demonstration on the manufacture of organic fertilizers from agricultural waste and cow dung using EM-4, Mol, Trichoderma sp, 2. demonstration of making local microorganisms (MOL), 3. analyzing nutrient elements of organic fertilizers, and 4. a demonstration plot of organic spinach and water spinach using organic fertilizers from three different organizer depupuk, namely: EM4, fruit mole, and a mixture of both. The results achieved were: organic fertilizer processing methods, and quality organic fertilizers with the highest average nutrient content of fruit mole samples (N = 1,823%, P = 1,717%, K = 0.757%, Mg = 0.742, C. organic 27,400 , Organic matter = 47.237, and the highest C / N = 39.645%. The demonstration plot of organic fertilizer from three organic fertilizer samples obtained that the use of fruit moles as organizer depupuk resulted in the best growth and yield of spinach and kale wet weight.